Practical Assessment of Synchronous Generator Dynamic Model Parameters - Ažubalis, M.; Ažubalis, V.; Jonaitis, A. (Elektronika ir Elektrotechnika, 2010)
The paper presents analysis of evaluation methods of synchronous generator dynamic model parameters according to field test data. The list of parameters of the dynamic model for analysis of electromechanical transient processes and stability conditions in power systems is presented. The parameters of direct and quadrature axes can be evaluated according to frequency response test applied to the stopped generator. Regime tests of operating generator can be used for evaluation of direct axis parameters as well as for value of inertia constant. The open circuit characteristic is used for assessment of saturation characteristic. The methodic of parameters’ evaluation is created and equations for their evaluation according to field test data are presented.